China's leaders from Mao to now - Shambaugh, David L. (Cambridge, United Kingdom Polity Press, 2021)
"A world-renowned Sinologist explores China's modern history through the lives of its leaders"--
On China's leaders and leadership -- Mao Zedong : populist tyrant -- Deng Xiaoping : pragmatic leninist -- Jiang Zemin : bureaucratic politician -- Hu Jintao : technocratic apparatchik -- Xi Jinping : modern emperor -- China's leaders in perspective.
Includes bibliographical references and index.
Keywords: Zhongguo gong chan dang. -- Zhong yang wei yuan hui -- Biography; Heads of state -- China -- Biography; Statesmen -- China -- Biography; China -- History -- 1949-.; China -- Politics and government -- 1949-.